STUDI PENDIDIKAN INTERDISIPLINER: KEPUTIHAN PADA WANITA MUSLIMAH PERSPEKTIF MEDIS DAN FIKIH DALAM MENJALANKAN SHOLAT - Izzati, Jovita Nurul; Salsabila, Annisa; Muzdhalifah, Muzdhalifah; Satra, Alihan (Jurnal Al-Fatih, 2025)
Leucorrhea is a common biological condition experienced by women, categorized medically into physiological (normal) and pathological (abnormal) types. This phenomenon often raises confusion and concern, especially regarding its implications on Islamic acts of worship, such as prayer (sholat), which requires ritual purity (thaharah) as a core prerequisite. Thus, understanding leucorrhea from a medical standpoint is essential to distinguish its types, as well as examining how Islamic jurisprudence (fiqh) interprets this condition in relation to the validity of worship. This study adopts a descriptive-qualitative approach through literature review, analyzing medical texts and classical to contemporary fiqh sources. It focuses on three main areas: the definition and classification of leucorrhea in medical science, scholarly Islamic views regarding its purity and impact on ritual practices, and a correlative analysis to synthesize both perspectives. The study finds diverse opinions among scholars on whether leucorrhea is considered impure and whether it nullifies ablution, with views often influenced by the medical characteristics of the discharge. By applying the maqasid al-shariah framework prioritizing the preservation of religion and health this research proposes balanced and wise solutions. Women experiencing physiological leucorrhea may continue to perform their religious duties without compromising their spiritual or physical well-being. It is hoped that this study serves as a practical and scholarly reference for Muslim women, religious authorities, medical professionals, and the wider Muslim community.